2021
DOI: 10.3389/fpls.2021.641717
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Pellucidin A in Peperomia pellucida (L.) HBK

Abstract: Peperomia pellucida (L.) HBK (Piperaceae) (“jabuti herb”) is an herbaceous plant that is widespread in the tropics and has several ethnomedicinal uses. The phytochemical study of leaf extracts resulted in the isolation of 2,4,5-trimethoxycinnamic acid, 5,6,7-trimethoxyflavone, 2,4,5-trimethoxystyrene, 2,4,5-trimethoxybenzaldehyde, dillapiol, and sesamin in addition to pellucidin A. The co-occurrence of styrene and cyclobutane dimers suggested the formation of pellucidin A by a photochemical [2+2] cycloaddition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 101 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…In addition, eupatoriochromene may be related to the process of maturation and development of inflorescences. This hypothesis is supported by published articles on the effect of eupatoriochromene on ontogenesis [113], as well as other chromenes, including in Piperaceae species [114,115]. Still, in the late 1980s, a study suggested that chromenes can act both in promoting the development of the reproductive structures of plant species, and jointly, in promoting the protection of floral organs [116,117].…”
Section: Discussionmentioning
confidence: 87%
“…In addition, eupatoriochromene may be related to the process of maturation and development of inflorescences. This hypothesis is supported by published articles on the effect of eupatoriochromene on ontogenesis [113], as well as other chromenes, including in Piperaceae species [114,115]. Still, in the late 1980s, a study suggested that chromenes can act both in promoting the development of the reproductive structures of plant species, and jointly, in promoting the protection of floral organs [116,117].…”
Section: Discussionmentioning
confidence: 87%
“…In traditional medicine, it is widely used in South American and Asian countries due to its antihypertensive, antimicrobial, analgesic, anti-inflammatory, antipyretic, antidiabetic, and antioxidant properties [ 15 , 16 ]. These characteristics allow classifying this species as the most chemically studied within the genus Peperomia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these species are used in traditional medicine to treat various ailments, including respiratory disorders, infections, and headaches. It has also been shown that some species, such as Peperomia inaequalifolia , in addition to its ornamental use, have important antibacterial and antifungal properties [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%